VALUE CHAIN ANALYSIS ON KANGKONG SEED PRODUCTION in PT EAST WEST SEED INDONESIA (EWINDO) - Supti, Dudin; Rujito, Hari; Kustiari, Tanti (Universitas Muhammadiyah Jember, 2019)
This research was conducted to analyze the condition and governance value chain of kangkong in Ewindo, especially in seed production so that the area of constraints can be identified and raises opportunities for upgrading. The objectives of this study include: 1) conducting value chain mapping, 2) analyzing water spinach seed production business, 3) knowing value chain governance, and 4) developing improvement strategies. This is descriptive research by using value chain analysis, value chain governance analysis, cost-benefit analysis, and upgrading strategy. The results show that the value chain governance between Ewindo and farmers is captive, where Ewindo as the lead company is required to have ethical leadership to ensure that farmers receive fair and equal treatment. By the highest benefit-cost ratio 1.63, generally, the contract farming is profitable, except in the new region (Tuban) that the farmers still need to improve their cultivation competencies. Some constraints in the value chain such as transportation facilities, product quality and weather, resulted both economic and social upgrading opportunities, i.e.: product quality improvement through product quality training; the provision of large-capacity and routine transportation; scheduled field schools for new farmers; and increasing strong social relationship with the farmers through family gatherings, achievement awards and initiation of climate index-based insurance.